Effects of rainfall, number of male inflorescences and spikelets on the population abundance of Elaeidobius kamerunicus (Coleoptera: Curculionidae) - Nurul Fatihah A.L.; Muhamad Fahmi M.H.; Luqman H.A; Syarifah Nadiah S.M.D.; Teo, T.M.; Izfa Riza Hazmi; Idris A.B. (Penebit Universiti Kebangsaan Malaysia, 2019)
Elaeidobius kamerunicus was first introduced to Malaysia from Cameroon as an oil palm pollinator in 1981. Since then, oil palm pollination has improved and the need for assisted pollination has reduced. Fruit set development and fruit production also saw significant improvements, until a reported decline that began in the late 1980s. Several factors may have contributed to such decline, but most researchers believe it is due to the low E. kamerunicus population. Therefore, a study was conducted to determine whether the amount of rainfall and the number of male inflorescences and spikelets influenced the population abundance of E. kamerunicus in Ladang Lekir, Perak, Malaysia. Sampling was performed each month in oil palm subplots, three for each age of palm age, from October 2015 to September 2016. A total of nine spikelets (three from the top, middle and base of a male inflorescence) were randomly selected from each male inflorescence on each chosen palm. They were cut early in the morning to avoid the weevil’s most active time, thus making collection easier. The number of weevils congregating on each spikelet was then counted. The average number of E. kamerunicus per hectare (ha) living on oil palms aged four and six were 21,086 and 25,712, respectively. The amount of rainfall and the number of male inflorescences and spikelets were found to positively correlate with the E. kamerunicus population. The number of male inflorescences showed strong correlation with the E. kamerunicus population. However, in-depth study is needed to determine the relationship between E. kamerunicus and fruit set.